Percepção dos profissionais de um Centro de Saúde Escola referente à atuação na área de Nutrição - Watanabe, Lígia Moriguchi [UNESP]; Almeida, Margareth Aparecida Santini de [UNESP]; Morita, Ione [UNESP] (My University, 2013)
In this study, we aimed to identify the perception of professionals working at a School-based Health Center (SBHC) regarding nutritional assistance. The methodological approach was qualitative. Semi-structured interviews with open questions and audio recordings were carried out with participants’ consent. Professionals who are directly or indirectly involved in the nutrition field were interviewed. Analysis of the given statements consisted in identifying recurring speech cores, seeking clarification of content and ensuring the understanding of the professionals’ perceptions. In the group of 17 respondents, aged 24 to 63, 70.6% were women. One of the identified core themes was the multidisciplinary team. It presents positive aspects because it allows the contact between different professional health areas. Regarding the negative aspects, the small number of nutritionists in the service should be highlighted. Another identified core was the need for works that transcend the service, to complement and reinforce information on food. Furthermore, health education makes a difference to nutrition and other areas as well. In this sense, proposal of new areas and strategies beyond the boundaries of the School-based Health Center would allow to reach a greater number of people and increase knowledge in the nutritional field and consequently individual autonomy.

Este estudio tuvo como objetivo identificar la percepción de los profisionales de un Centro de Salud Escolar con relación a su atuación en el área de nutrición. La metodología utilizada fue cualitativa mediante entrevistas semiestructuradas, con preguntas abiertas y grabadas en audio, a los profesionales que actúan directa o indirectamente con cuestiones relativas al área de nutrición. Se analizaron los testimonios de los testimonios de los sujetos identificando núcleos recurrentes en sus discursos, buscando explicitar los contenidos, garantizando la comprensión de sus percepciones. De los 17 profesionales entrevistados, el 70,6% fueron mujeres de entre 24 y 63 años. Uno de los núcleos temáticos identificados fue el trabajo en equipo multidisciplinario, que presentó aspectos positivos porque permite el contacto entre las diferentes áreas profesionales de la salud. Entre los aspectos negativos, algunos resaltaron el reducido número de nutricionistas en servicio. La Educación en Salud fue destacada como un aspecto diferencial para todas las áreas de actuación, pero sobre todo para la nutrición. En este sentido, las propuestas de nuevos espacios y estrategias que trascendieran el servicio permitirían alcanzar un mayor número de personas, ampliando el conocimiento general en el área de nutrición y, en consecuencia, la autonomía individual.

O presente trabalho objetivou identificar a percepção dos profissionais de um Centro de Saúde Escola referente à atuação na área de Nutrição. A metodologia desenvolvida foi qualitativa mediante entrevistas semiestruturadas, com perguntas abertas e audiogravadas dos profissionais que atuam direta ou indiretamente com questões relacionadas à área de Nutrição. A análise das falas dos sujeitos foi realizada por meio da identificação de núcleos recorrentes nos discursos, buscando a explicitação dos conteúdos, garantindo a compreensão da percepção dos profissionais. No grupo de 17 profissionais entrevistados, 70,6% foram mulheres, com faixa etária entre 24 e 63 anos. Um dos núcleos temáticos identificados foi o trabalho em equipe multidisciplinar, que apresenta aspectos positivos, porque permite o contato com as diferentes áreas profissionais da saúde. Em relação aos aspectos negativos, alguns ressaltaram o número reduzido de Nutricionistas no serviço. A educação em saúde é destacada como um diferencial para todas as áreas de atuação, sobretudo para a Nutrição. Nesse sentido, propostas de novos espaços e estratégias que transcendessem o serviço possibilitariam atingir um maior número de pessoas, ampliando-se o conhecimento geral na área de Nutrição e, consequentemente, a autonomia individual.
Professionals’ perception at a School-based Health Center (SBHC) regarding nutritional assistance
Keywords: Nutrition; Perception; Basic health care; Nutrición; Percepción; Atención básica; Nutrição; Percepção; Atenção básica